2023
DOI: 10.3389/ijph.2023.1606032
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Psychosomatic Complaints in Adolescence: Findings From a Swedish Cohort Study

Sara Brolin Låftman,
Viveca Östberg,
Jonas Raninen

Abstract: Objectives: To examine the cross-sectional and longitudinal associations between generalised and institutional trust and psychosomatic complaints in mid and late adolescence.Methods: Data were derived from the Swedish cohort study Futura01, using survey information collected amongst 3,691 grade 9 students (∼15–16 years, t1) who were followed-up 2 years later (∼17–18 years, t2). Registry information on sociodemographic characteristics was linked to the data. Linear regression analyses were performed. The longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…The five items showed acceptable internal consistency (Cronbach’s alpha: wave 1: 0.62; wave 2: 0.67). In accordance with previous studies based on the same data [ 19 , 26 ], we removed item b as this improved the internal consistency (Cronbach’s alpha wave 1: 0.71; wave 2: 0.73). We calculated the mean value of items a, c, d and e for participants who responded to at least three of these.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…The five items showed acceptable internal consistency (Cronbach’s alpha: wave 1: 0.62; wave 2: 0.67). In accordance with previous studies based on the same data [ 19 , 26 ], we removed item b as this improved the internal consistency (Cronbach’s alpha wave 1: 0.71; wave 2: 0.73). We calculated the mean value of items a, c, d and e for participants who responded to at least three of these.…”
Section: Methodsmentioning
confidence: 87%
“…Building on a previous article on trust and psychosomatic complaints in adolescents [ 19 ], the aim of the present study was to examine the links between generalised and institutional trust in adolescence and depression and anxiety symptoms in young adulthood in a Swedish cohort. The results showed that generalised trust at ages 15–16 and 17–18 was inversely associated with depression and anxiety symptoms at age 20–21.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations